EFFECTS OF BIRTHBALL RELAXATION ALTERNATIVES AND AROMA THERAPY ON THE PROGRESS AND SATISFACTION OF LABOR IN THE DISTRICT NORTH TAPANULI IN 2023 - simbolon, juana linda (Universitas Aisyah Pringsewu, 2023)
Giving birth is the highest expression of female sexuality, using the same hormones (oxytocin, prolactin, and endorphin. Childbirth and sex are interrelated, and how she experiences the birthing process. Midwives must understand beneficial and detrimental actions during the birthing process, such as reducing negative emotional reactions, and physical reactions mother to pain so that efforts to create physical and emotional comfort are needed. WHO emphasizes patient satisfaction as a means of secondary prevention of maternal death by preventing and reducing the impact of the birth process. The aim of this research was to analyze the effect of birth ball exercises and aroma therapy on maternal progress and satisfaction in labor. This type of research was experimental pre and post-test with a control group design. The sample size in this study was 34 mothers in labor consisting of 17 mothers in the intervention group and 17 mothers in the control group. Analysis using parametric analysis test T-test. Test with degrees of 95% confidence. The results of this study show that there is a difference in the length of time for the first stage in the control and intervention groups, p-value 0.02 0.05. The results of this study show that the intervention group generally felt satisfied with their delivery. In developing midwifery care, we can provide birth ball exercises and orange aroma therapy to speed up the first stage and as a non-pharmacological therapy option that supports pharmacological therapy for mothers in labor.